2004
DOI: 10.1007/s00384-004-0585-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of apoptosis-related proteins in rat with induced colitis

Abstract: Our findings suggest that expression of apoptosis markers is related to the degree of colitis and show that apoptosis is sustained by both p53 and FasR/FasL pathways, depending on the phase of colitis development. Moreover, the lack of TG staining in typical apoptotic bodies may account for a perturbation of the cross-linked apoptotic envelope that may be an important determinant in the development of immune response in ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…IBD evoke a damage‐repair process accompanied by the activation of apoptotic genes. Previous studies have shown significant apoptosis in colonic epithelial cells during mild inflammation induced by TNBS, and it is suggested that expression of apoptosis markers is related to the degree of colitis ( Yue et al ., 2001 ; D'Argenio et al ., 2004 ). In addition, deregulated apoptosis seems to be a major cause of the impaired barrier function, leading to the invasion of pathogenic microorganisms, and to an increase of leukocyte survival with exacerbation of the disease ( Yue et al ., 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…IBD evoke a damage‐repair process accompanied by the activation of apoptotic genes. Previous studies have shown significant apoptosis in colonic epithelial cells during mild inflammation induced by TNBS, and it is suggested that expression of apoptosis markers is related to the degree of colitis ( Yue et al ., 2001 ; D'Argenio et al ., 2004 ). In addition, deregulated apoptosis seems to be a major cause of the impaired barrier function, leading to the invasion of pathogenic microorganisms, and to an increase of leukocyte survival with exacerbation of the disease ( Yue et al ., 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that the specific inhibitor of K ϩ channels 48F10 can prevent apoptosis in enterocytes may have an important clinical implication. Intestinal disorders such as ulcerative colitis (3,15,44), coeliac disease (2,22,25), necrotizing enterocolitis (18,28), and microvillus inclusion disease (10) are associated with increased levels of enterocyte apoptosis. Specific inhibitors of enterocyte K ϩ channels may be useful in preventing or modulating gut barrier failure associated with these inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial cell injury in inflamed colonic mucosa in IBD is due to the apoptotic cell death [26]. p53 is one of the major regulators in apoptosis and its protein level increases in the colon mucosa of IBD [26].…”
Section: Discussionmentioning
confidence: 99%
“…p53 is one of the major regulators in apoptosis and its protein level increases in the colon mucosa of IBD [26]. Increased apoptosis in DSS-induced colitis may bring a destruction of the epithelial barrier function and facilitate the mucosal invasion of harmful intestinal bacteria, which leads to the chronic phase of colitis.…”
Section: Discussionmentioning
confidence: 99%